Phosphoproteomic profiling reveals ABA‐responsive phosphosignaling pathways in Physcomitrella patens. (23rd April 2018) - Amagai, Anna; Honda, Yoshimasa; Ishikawa, Shinnosuke; Hara, Yurie; Kuwamura, Mayuri; Shinozawa, Akihisa; Sugiyama, Naoyuki; Ishihama, Yasushi; Takezawa, Daisuke; Sakata, Yoichi; Shinozaki, Kazuo; Umezawa, Taishi
Summary: Abscisic acid (ABA) and its signaling system are important for land plants to survive in terrestrial conditions. Here, we took a phosphoproteomic approach to elucidate the ABA signaling network in Physcomitrella patens, a model species of basal land plants. Our phosphoproteomic analysis detected 4630 phosphopeptides from wild‐type P .  patens and two ABA‐responsive mutants, a disruptant of group‐A type‐2C protein phosphatase (PP2C; ppabi1a/b ) and AR7, a defective mutant in ARK, identified as an upstream regulator of SnRK2. Quantitative analysis detected 143 ABA‐responsive phosphopeptides in P .  patens . The analysis indicated that SnRK2‐mediated phosphorylation and target motifs were partially conserved in bryophytes. Our data demonstrate that the PpSnRK2B and AREB/ABF‐type transcription factors are phosphorylated in vivo in response to ABA under the control of ARK. On the other hand, our data also revealed the following: (i) the entire ABA‐responsive phosphoproteome in P .  patens is quite diverse; (ii) P .  patens PP2C affects additional pathways other than the known ABA signaling pathway; and (iii) ARK is mainly involved in ABA signaling. Taken together, we propose that the core ABA signaling pathway is essential in all land plants; however, some ABA‐responsive phosphosignaling uniquely developed in bryophytes during the evolutionary process. Significance Statement: Phosphoproteomic profiling in Physcomitrella patens revealed ABA‐dependent phosphosignaling, leading us to compare ABA responses between bryophytes and higher plants at the signaling level.